Culturable bacterial microbiota of Plagiodera versicolora (L.) (Coleoptera: Chrysomelidae) and virulence of the isolated strains - Demirci, Meryem; Sevim, Elif; Demir, İsmail; Sevim, Ali (Folia microbiologica, 2013)
Plagiodera versicolora (Laicharting, 1781) (Coleoptera: Chrysomelidae) is an important forest pest which damages many trees such as willow, poplar, and hazelnut. In order to find new microbes that can be utilized as a possible microbial control agent against this pest, we investigated the culturable bacterial flora of it and tested the isolated bacteria against P. versicolora larvae and adults. We were able to isolate nine bacteria from larvae and adults. The isolates were characterized using a combination of morphological, biochemical, and physiological methods. Additionally, we sequenced the partial sequence of the 16S rRNA gene to verify conventional identification results. Based on characterization studies, the isolates were identified as Staphylococcus sp. Pv1, Rahnella sp. Pv2, Rahnella sp. Pv3, Rahnella sp. Pv4, Rahnella sp. Pv5, Pantoea agglomerans Pv6, Staphylococcus sp. Pv7, Micrococcus luteus Pv8, and Rahnella sp. Pv9. The highest insecticidal activity against larvae and adults was obtained from M. luteus Pv8 with 50 and 40 % mortalities within 10 days after treatment, respectively. Extracellular enzyme activity of the bacterial isolates such as amylase, proteinase, lipase, cellulose, and chitinase was also determined. Consequently, our results show that M. luteus Pv8 might be a good candidate as a possible microbial control agent against P. versicolora and were discussed with respect to biocontrol potential of the bacterial isolates.
Keywords: brouci; Peptide Hydrolases; Sequence Analysis, DNA; RNA, Ribosomal, 16S; Micrococcus luteus; lipasa; proteasy; virulence; amylasy; Microbial Sensitivity Tests; fenotyp; Rahnella; Biological Control Agents; Microbiota; mikrobiota; chitinasy; Chitinases; Cellulose; Phenotype; RNA ribozomální 16S; zvířata; Virulence; Coleoptera; Lipase; celulosa; Amylases; sekvenční analýza DNA; larva; Larva; Pantoea; biologická ochrana; mikrobiální testy citlivosti; Staphylococcus; Animals